2022
DOI: 10.1038/s41598-022-07333-x
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic wounds treated with cold atmospheric plasmajet versus best practice wound dressings: a multicenter, randomized, non-inferiority trial

Abstract: The use of phase-adapted wound dressings represents best practice (BP) in chronic wound treatment. However, efficacy is often limited and associated care requirements are high. Cold atmospheric plasmajet (CAP-jet) is a promising new therapeutic tool for these wounds. In the present multicenter, randomized, open-label, prospective, clinical trial, non-inferiority of the CAP-jet versus BP was assessed in 78 patients with infected or non-infected chronic wounds of different etiology. Primary outcome measure was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
(67 reference statements)
0
8
0
3
Order By: Relevance
“…Four trials [ 19 , 22 24 ] reported the reduction of wound area (unit: cm 2 ), with 98 patients in CAP group and 91 in control group. As the heterogeneity was detected ( I 2 = 18%), a fixed-effects model was used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four trials [ 19 , 22 24 ] reported the reduction of wound area (unit: cm 2 ), with 98 patients in CAP group and 91 in control group. As the heterogeneity was detected ( I 2 = 18%), a fixed-effects model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of included studies are presented in Table 1. Eight studies [12][13][14][15][16][17][18][19][20] were conducted in Germany, three in Iran [21][22][23], one in Austria [24], and one in Thailand [20]. The 13 included studies involved a total of 477 participants, who were randomized either into CAP treatment group or control group.…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of argon plasma on the growth of soybean sprouts and the regulatory mechanism of energy metabolism were studied 21 . Although cold plasma has great potential advantages in various industrial fields such as surface treatment 22 , seed germination 23 , 24 , wounds healing 25 , etc., the investigation of cold plasma applications in the poultry industry is still in its early stages 26 .…”
Section: Introductionmentioning
confidence: 99%